1987
DOI: 10.1099/00221287-133-6-1435
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Extracellular Glucosyltransferase from Streptococcus mutans Serotype b (Subspecies rattus)

Abstract: An extracellular glucosyltransferase (GT-S) synthesizing water-soluble glucan was purified from the culture supernatant of Streptococcus mutans BHT (serotype b, subsp. rattus) by DEAE-Sepharose chromatography and preparative isoelectric focusing. The Mr of the enzyme was 155,000 and the pI was 4.5. The GT-S had a specific activity of 10.2 i.u. (mg protein)-1, an optimum pH of 6.0 and a Km value of 0.8 mM for sucrose, and was activated twofold by dextran T10. The GT-S was immunologically partially identical wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Complementation with a wild-type copy of rex , including its promoter region, on shuttle vector pDL278 (LeBanc & Lee, 1991) partially restored the phenotype of the wild-type (Figure 3). A phenol-sulfuric acid assay was also used to measure total glucans in the biofilms (Mukasa, et al , 1985, Kumada, et al , 1987, Ausubel, et al , 1992, Werning, et al , 2008). As expected, TW239 biofilms contained more than 2-fold glucose polymers than the parent strain, with an average of 30.62 (±5.7) µg/ml for UA159 and 72.45 (±15.85) µg/ml for TW239 ( P <0.001), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementation with a wild-type copy of rex , including its promoter region, on shuttle vector pDL278 (LeBanc & Lee, 1991) partially restored the phenotype of the wild-type (Figure 3). A phenol-sulfuric acid assay was also used to measure total glucans in the biofilms (Mukasa, et al , 1985, Kumada, et al , 1987, Ausubel, et al , 1992, Werning, et al , 2008). As expected, TW239 biofilms contained more than 2-fold glucose polymers than the parent strain, with an average of 30.62 (±5.7) µg/ml for UA159 and 72.45 (±15.85) µg/ml for TW239 ( P <0.001), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To measure the extracellular glucose polymers in biofilms, a phenol-sulfuric acid assay was used with known concentrations of glucose as the standards (Mukasa, et al , 1985, Kumada, et al , 1987, Ausubel, et al , 1992, Werning, et al , 2008). Briefly, 3-day biofilms were grown in BMGS on glass slides in 50 ml tubes as described elsewhere (Phan, et al , 2000, Wen, et al , 2010, Wen, et al , 2010).…”
Section: Methodsmentioning
confidence: 99%
“…2), was free of the PI 7.4 and 8.4 GTF-S of similar M , (Fig. l), (as were the washed cells) and did not react with anti-GTF-S sera from serotype c and b streptococci (Mukasa et al, 1985;Kumada et al, 1987) (data not shown). These observations indicate that the preparation was not detectably contaminated with such proteins as GTF-S which might coprecipitate with GTF-I upon the IEF (seconddimension) run of the 2-DE.…”
Section: Discussionmentioning
confidence: 99%
“…After two washes with 75% ethanol containing 0.15 M-NaCl, the polysaccharides were analysed by gas-liquid chromatography (Mukasa et al, 19826) with dextran T10 (Pharmacia) and inulin (Tokyo Kasei) as standards. Total polysaccharides were measured by the phenol/sulphuric acid method (Dubois et al, 1956) with glucose as a standard, and fructan was measured according to the method of Van Handel (1967) as described by Kumada et al (1987) using fructose as a standard. The amount of glucan was estimated by subtracting the amount of fructan from the amount of total polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…Tsumori et al, 1983b;Koga et al, 1983;McCabe, 1985;Mukasa, 1986). In Streptococcus rattus (mutans group serotype 6) and Streptococcus mutans (mutans group serotypes c, e andf), adherent insoluble polysaccharide is synthesized cooperatively by two GTFs; GTF-I, which synthesizes an insoluble glucan, and GTF-S, which synthesizes a soluble glucan ; and probably fructosyltransferases, which synthesize an inulin-type fructan (Scales et al, 1975;Mukasa et al, 1982bMukasa et al, , 1985Mukasa et al, , 1989Kenny & Cole, 1983;Mukasa, 1986;Shimamura et al, 1987;Kumada et al, 1987;Tsumori et al, 1989).…”
Section: Introductionmentioning
confidence: 99%